2004
DOI: 10.1002/bdm.470
|View full text |Cite
|
Sign up to set email alerts
|

Evidence coverage and argument skills: cognitive factors in a juror's verdict choice

Abstract: Juror reasoning and verdict choice have been explored variously as functions of argument skill and the overall story representation of the evidence on which verdict choices are based. This study investigates the proportion of testimony covered in the justification of a verdict choice and its relationship with argument skill, narrative explanation or evidence-based argument, and certainty about verdict choice. Each of these variables was also compared with the verdict choice. People serving jury duty justified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…This justifies the assumption of the previously described juror study that personal certainty appears to be a function of personal epistemology and not particular content. Like in the other study, those most certain chose the maximum verdicts in both cases (Weinstock & Flaton, 2004). That is, those with less skill seem to be able to consider only a more narrow range of arguments for alternatives.…”
Section: Complex Argument Constructionmentioning
confidence: 57%
“…This justifies the assumption of the previously described juror study that personal certainty appears to be a function of personal epistemology and not particular content. Like in the other study, those most certain chose the maximum verdicts in both cases (Weinstock & Flaton, 2004). That is, those with less skill seem to be able to consider only a more narrow range of arguments for alternatives.…”
Section: Complex Argument Constructionmentioning
confidence: 57%
“…Jurors are chosen to represent the average person, and people do not receive special training in juror reasoning. Nevertheless, some jurors demonstrate greater skill in reasoning in their task (Kuhn et al, 1994;McCoy, Nunez, & Dammeyer, 1999;Weinstock & Cronin, 2003;Weinstock & Flaton, 2004). Such differences have been found to be predicted by general epistemological understandings of the nature of knowledge and how it is justified (Kuhn et al, 1994;Weinstock & Cronin, 2003).…”
Section: The Relationship Between Epistemological Understanding and Jmentioning
confidence: 91%
“…And, as will be examined in detail in this paper, average citizens who are neither lawyers nor judges are asked to serve as jurors and construct supportable claims and meaningful decisions about what happened. Some people perform the task of juror reasoning better than others do (Kuhn, Weinstock, & Flaton, 1994;Weinstock & Cronin, 2003;Weinstock & Flaton, 2004). Do they, like experts in a field, better represent the knowledge, have better epistemic understanding of the task at hand, and have an idea of what the ideal reasoner would do to Learning and Individual Differences 19 (2009) Differences in everyday reasoning and informal argument have been found to rest on differences in such folk theories of knowledge (Kuhn, 1991;Weinstock & Cronin, 2003;Weinstock, Neuman, & Glassner, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…However, other research (Kuhn, Weinstock, & Flaton, 1994;Weinstock & Flaton, 2004) has found that those jurors who express the greatest degree of certainty in their verdicts typically consider less evidence when making their decision than do jurors who report greater uncertainty. If I find that relationship to emerge in the current study, then I should expect to find that angry participants who detect fewer inconsistencies should report the greatest degree of confidence in their verdict decisions.…”
Section: Verdict Confidence As a Results Of Processing Stylementioning
confidence: 99%
“…Other examples include the use of technically incorrect lay definitions of legal rules when determining verdicts as well as the comparison of case facts to "crime prototypes" which are each juror's idealized, generic expectation of what the crime typically involves (V. L. Smith, 1991). Jurors are also vulnerable to less cognition-oriented heuristics such as placing undue emphasis on the complexity of the testimony given by experts or people perceived to be in positions of authority (Cooper, Bennett, & Sukel, 1996), the physical attractiveness of the defendant (Lieberman, 2002), the sheer number of plaintiffs (Horowitz & Bordens, 2000), and the volume of evidence entered (Weinstock & Flaton, 2004). The more jurors rely on these sorts of heuristics, the less likely they are to be able to reason capably and thoroughly, to understand evidence both singularly and as a part of a larger picture, and to apply their conclusions towards a verdict in accordance with judicial instruction (Greene & Ellis, 2007).…”
Section: Civil Justice System Overviewmentioning
confidence: 99%